Automated Attendance System using RFID and IoT - C., Dhanush; Chowdhury, Sumit Singha; Shekadar, Aparna K. (Journal of ISMAC, 2025)
In educational institutions and workplaces, the manual tracking of attendance can be subject to human error, be time-consuming, and be administratively taxing. In recent years, IoT and wireless technologies have developed automated attendance tracking systems based on Radio Frequency Identification (RFID). In this document, we describe a cloud-based RFID attendance tracking system to improve accuracy, minimize manual effort, and enable real-time tracking. The hardware system uses a NodeMCU (ESP32) microcontroller, coupled with an RFID reader module, an LCD module, LED indicators, and an NTP server to maintain accurate time. The attendance information is gathered through unique RFID tags that are directly linked to user profiles in the Firebase cloud. When the RFID tag is in range and scanned, the app will verify the user, and then read, track, and log the UID, name, timestamp, and email of the user. If an unauthorized person or tag is scanned, the system will request permission to scan from an admin user, enhancing the security and reliability of the system. Admin users can view all users and their attendance, as well as view attendance in real-time, as dashboards, graphs, and analytic reports via the web-based portal of the attendance system. This system is designed to be scalable and adaptable for use in a variety of settings, including educational institutions and office spaces. Not only does it simplify the management of attendance, but it can also provide valuable data and details regarding patterns of attendance, which help verify and justify the use of resources and determine performance. The solution offers secure access, ease of use, and rapid data access and control, which improves the overall management of the institution.